CEFOPERAZONE (T-1551) IN THE FIELD OF DERMATOLOGY - AKIYAMA, HISANORI; SUWAKI, MASAO; ARATA, JIRO; YAMAMOTO, YASUO; KASHIWA, NAOHIRO; NOHARA, NOZOMI (CHEMOTHERAPY, 1980)
1) MICs of cefoperazone (CPZ, T-1551), cefazolin, cephalothin and cephaloridine against 32 strains of Staphylococcus aureus isolated from the lesions of skin infection were studied. MIC of CPZ was inferior to cefazolin, cephalothin and cephaloridine. 2) Serum and skin levels of CPZ (20mg/kg im) were determined in rats at 1/4, 1/2, 1, 2 and 4 hours. Serum levels were 9.8±3.02, 6.2±2.30, 0.66±0.19μg/ml at 1/4, 1/2 and 1 hour, respectively. The corresponding skin levels were 4.6±1.35, 3.9±1.39, 1.08±0.37μg/g. At 2 and 4 hours those levels were trace (wet skin)(n=4). 3) CPZ was used clinically in 5 cases of skin infection with the following result: excellent in 3 cases, poor in 1 case. In 1 case evaluation was not possible. Any side effects were not observed.